Building PHP applications with Symfony, CakePHP, and Zend Framework - Porebski, Bartosz; Przystalski, Karol; Nowak, Leszek; Safari eBooks (Hoboken, N.J. : Wiley ; Chichester : Wiley [distributor], 2011)
Presents a comparison of the three open source frameworks and how they can be used to create PHP Web sites.
Description based on print version record.
Includes index.
Keywords: PHP (Computer program language); Application software -- Development; Web sites -- Design; Electronic books